Thyroid Storm Presenting as Gastroenteritis - Kendall Rader; Roderick Morrison (Association of American Medical Colleges, 2011)
Abstract Simulation is an effective way to portray real emergency medicine pathology to residents in a controllable yet realistic environment. This case features a 31-year-old female with undiagnosed Grave's disease that progresses to full thyroid storm as a result of viral gastroenteritis. An outline of the case, instructor's guide, and a PowerPoint presentation are included to aid in simulation facilitation. The session requires a realistic emergency department acute care room, and actors to play the role of emergency room nurse and the patient's roommate. This module, including both the simulation session and debriefing, should take approximately 30 to 60 minutes to complete. This particular case was reviewed by the faculty responsible for the simulation program at Indiana University School of Medicine Emergency Medicine Residency Program. Simulation has proven to be an effective learning tool for the residents, students and faculty within the program. We have found that this method of learning creates real-life experience in a hands-on environment.